Control and Resistance in a Young Adult Dystopian Fiction: A Foucauldian Reading of Marie Lu’s Legend - Nur Amalina (Passage, 2015)
This research attempts to discover how a young adult dystopian novel entitled Legend by Marie Lu portrays a totalitarian government controls its subject and the way young adult characters resists to it. This research employs Foucault’s discipline technique and categorization of resistance. The findings shows that the controlling strategies in the society within Legend reflect two of Foucault’s techniques: geneses organization, and distribution system. Additionally, the controlling strategy is supported by terror and knowledge concealment. For the young adult resistance aspect, the characters’ resistance acts are found to be directed towards subjection and domination. The resistance is manifested through actions which embody two major characteristics, aggressive or submissive. In addition, Legend also demonstrates the use of discourse as a device to revolt. Ultimately, Legend appears to inherit the didactic nature of young adult dystopian literature as it cast warning about absolutism of certain group, the danger of a certain policy in current society, and the importance of knowledge, individuality and freedom of choice.Keywords: control, resistance, discipline, dystopia, young adult literature